The association between physical fitness level and rate and severity of injury and illness in youth elite athletes - Moseid, C. H.; Myklebust, G.; Slaastuen, M. K.; Bar-Yaacov, J. B.; Kristiansen, A. H.; Fagerland, M. W.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Youth elite athletes often double their training and competition load after enrollment into specialized sport academy high school programs. The least fit athletes may be exposed to an excessive and too rapid increase in training load, with negative adaptations such as injury and illness as a consequence. In this study, our aim was to determine whether these least fit athletes were at greater risk of injury or illness during their first school year. Participants were 166 youth elite athletes (72% boys) from a variety of team, technical and endurance sports newly enrolled into specialized sport academy high schools. The Oslo Sports Trauma Research Center Questionnaire on Health Problems was used to self-report injuries and illnesses weekly for 26 weeks. Athletes completed the Ironman Jr physical fitness test battery at baseline, evaluating endurance, strength, agility and speed properties. We ranked the athletes based on their combined test scores, and identified the least fit quartile. The main outcome was the number and severity of health problems, comparing the least fit quartile of athletes to the rest of the cohort. Overall, the least fit quartile of athletes did not report more health problems (mean 3.7, 95% CI 3.0 to 4.4) compared to the rest of the cohort (3.6, 3.2 to 3.9). In conclusion, we demonstrated no association between low physical fitness level and injury and illness rate or severity in youth elite athletes after enrollment into a specialized sport academy high school program.